Immunomodulator Effect of Swarna Prashana (Oral Administration of Gold as Electuary) -A Conceptual Study - Garg, Naresh Kumar; Sharma, Dharmendra; chand, Trilok; bansal, Satynarayan (International Research Journal of Ayurveda & Yoga, 2022)
Swarna Prashana (the oral administration of gold as an electuary) is a unique Ayurvedic treatment in the field of children. The canonical textbook of Kaumarabhritya (paediatrics), Kashyapa Samhita, illustrates this unusual formulation in the setting of Lehana (licking procedure by electuary). It has been explained that gold should be triturated with water, honey, and Ghrita on a pre washed and clean stone facing east, and the semisolid concoction should be presented to the Shishu/infant. Swarna has been used in a variety of forms and doses throughout history, including raw gold, pure metal, gold foils, red colloidal solution, Swarna Patra, Swarna Parpati, and Bhasma, to name a few. Swarnaprashana is a practise in which Swarna and herbs are given to children orally in the form of a liquid, semi-solid, or paste. Madhu + Ghrita + Abharak bhasma + Swarna Bhasma + Swarnamakshik bhasma + Brahmi Churna + Kantakari +Shankhpushpi +Haritaki +Haridra + Kootha are the constituents of Swarna prashana. In Present Conceptual study describe the Immunomodulator effect of Swarna Prashana in detail according to Ayurveda.